Pengaruh Penyakit Virus Mosaik dan Kuning Terhadap Hasil Panen Tanaman Kacang Panjang (Vigna sinensis L.) Di Desa Perean, Baturiti, Tabanan - NI NYOMAN ALIT PURWANINGSIH; NI MADE PUSPAWATI; I DEWA NYOMAN NYANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
Influence Mosaic Diseases and Yellow to Long Bean (Vigna sinensis L.)Production at Perean Village, Baturiti, TabananThis study aims to determine how far the influence of viral infection with symptoms of mosaic and yellow against a decrease in crop yield long beans. This research consists of four activities are: 1. Determining the spread of disease areas; 2. Observation and data collection; 3. Calculation yields; and 4. Data analysis. Design used was a randomized block design (RBD) with three treatments and nine replications.Research result show that long bean plants in several locations in Perean village infected by BCMV which has mosaic symptoms and MYMV which has yellow symptoms. Percentage of mosaic virus symptoms is higher than yellow virus. The average of percentage of mosaic virus symptoms was 42,85%, while yellow virus was 32,70%. Plant beans with yellow virus symptoms causes the highest yield loss which amounted to 53,87% and plants with symptoms of mosaic virus by 43,02% when compared with healthy plants. Based on these studies it is necessary dissemination of information, about the importance of sanitation and the use of healthy seeds to controlling the long bean’s viral infection to related parties.